Parvovirus Infection – Contemporary Issues in Epidemiology and Clinical Medicine - O. N. Nikishov; A. A. Kuzin; A. Yu. Antipova; I. N. Lavrent’eva (Эпидемиология и вакцинопрофилактика)
Parvovirus infection (PVI) is an important but little-known problem in the Russian Federation. Its clinical manifestations are characterized by different clinical entities that require differential diagnosis, as with other viral infections, as well as non-communicable diseases and epidemiological significance of PVI determined the prevalence of the development of epidemic outbreaks, mainly in organized groups. Medical and social - with teratogenic virus, as well as the possibility of its transmission at gematransfuziyah. The main risk groups - pregnant women, patients hematological profile. In the absence of recording and reporting the incidence of people is impossible to establish the scale of the spread of parvovirus infection. Crucial in this respect are laboratory studies that reveal the prevalence of its laboratory markers.